Identification of the mutation signature of the cancer genome caused by irradiation. (February 2021) - Kageyama, Shun-Ichiro; Du, Junyan; Kaneko, Syuzo; Hamamoto, Ryuji; Yamaguchi, Shigeo; Yamashita, Riu; Okumura, Masayuki; Motegi, Atsushi; Hojo, Hidehiro; Nakamura, Masaki; Tsuchihara, Katsuya; Akimoto, Tetsuo
Graphical abstract: Highlights: Sequencing showed de novo mutations in irradiated oesophageal cancer cells. Irradiated cells had hotspots for single nucleotide variants and indels. Single nucleotide variants originated from errors in double-stranded break repair. Mutation profiles of irradiated cells will help understand the cancer genome. Mutations signatures may help devise radio- and combination therapy for cancers. Abstract: Background and purpose: Ionising radiation causes mutations in the genomes of tumour cells and serves as a potent treatment for cancer. However, the mutation signatures in the cancer genome following ionising radiation have not been documented. Materials and methods: We established an in vitro experimental system to analyse the presence of de novo mutations in the cancer genome of irradiated (60 Gy/20 fr/4 weeks) oesophageal cancer cell lines. Subsequently, we performed whole-genome, chromatin immunoprecipitation, and RNA sequencing using untreated and irradiated samples to assess the damage to the genome caused by radiation and understand the underlying mechanism. Results: The irradiated cancer cells exhibited hotspots for the de novo 8502–12966 single nucleotide variants and 954–1, 331 indels on the chromosome. These single nucleotide variants primarily originated from double-stranded break repair errors, as determined using mutation signature analysis. The hotspots partially overlapped with the sites of H3K9 trimethylation, which are regions characterised by a weak capacity for double-stranded break repair. Conclusion: This study highlights the signature and underlying mechanism of radiation on the cancer genome.